2015
DOI: 10.1002/jcb.25045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐124 Regulates Neuronal Differentiation of Mesenchymal Stem Cells by Targeting Sp1 mRNA

Abstract: MicroRNAs play an important role in neuronal development and function. miR-124 is the most abundantly expressed miRNA in the nervous system. Several different mRNA targets have been proposed for miR-124, but the precise function of endogenous miR-124 and its mRNA targets remain to be further elucidated. Specificity protein 1 (Sp1) is a transcription factor that plays key roles in many cell processes including cell cycle. However, this transcription factor is nearly absent in differentiated neurons and a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Sp1 has previously been shown to be downregulated by miR‐128 in glioma cells where it has been proposed to repress Sp1 enhanced tumor formation and growth . In addition, miR‐124 has been reported to suppress Sp1 expression in mesenchymal stem cells induced to differentiate into neuron‐like cells . Our data indicate that miR‐124, ‐128, and ‐137 synergize to produce a stronger effect on Sp1 expression.…”
Section: Discussionsupporting
confidence: 54%
“…Sp1 has previously been shown to be downregulated by miR‐128 in glioma cells where it has been proposed to repress Sp1 enhanced tumor formation and growth . In addition, miR‐124 has been reported to suppress Sp1 expression in mesenchymal stem cells induced to differentiate into neuron‐like cells . Our data indicate that miR‐124, ‐128, and ‐137 synergize to produce a stronger effect on Sp1 expression.…”
Section: Discussionsupporting
confidence: 54%
“…Our data further suggest that the downregulation of Sox9 and Ptbp1 by miR‐124 is necessary for neuronal differentiation. Accordingly, Mondanizadeh et al reported an increase of miR‐124 expression during neurogenesis in adipose‐derived mesenchymal stem cells by targeting Sp1 mRNA (Mondanizadeh et al, ). miR‐124 targets cellular gene expression including repression of transcription factor Sox9 in SVZ stem cells (Cheng, Pastrana, Tavazoie, & Doetsch, ) and it reduces RNA‐binding protein PTBP1 (Makeyev, Zhang, Carrasco, & Maniatis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Mondanizadeh et al reported an increase of miR-124 expression during neurogenesis in adipose-derived mesenchymal stem cells by targeting Sp1 mRNA (Mondanizadeh et al, 2015).…”
Section: Stem Cells Express Master Regulatorsmentioning
confidence: 99%
“…Most recently, it was demonstrated that miR-124 is able to suppress Sp1 expression, which in turn affected the neuronal differentiation of mesenchymal stem cells [28]. miR-124 could directly target SCP1, which play a key role in the neuronal differentiation of ADSC [29].…”
Section: Discussionmentioning
confidence: 99%